2011
DOI: 10.1051/medsci/2011272163
|View full text |Cite
|
Sign up to set email alerts
|

Les syncytines

Abstract: Au cours de l'évolution, les vertébrés ont été exposés à de multiples vagues d'infection par les rétrovirus. Par leur capacité remarquable à intégrer leur ADN dans le génome de la cellule cible, certains rétrovirus se sont insérés dans la lignée germinale de leur hôte. Ils ont ensuite été transmis verticalement de génération en génération, de façon mendélienne. Suite à de nombreux événements d'amplification, ces rétrovirus endogènes (ou ERV pour endogenous retroviruses) forment maintenant des familles multigén… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These new genes, depending on their fitness with regard to fulfilling placental functions, were selected in place of the previously captured envelopes, replacing them following a classical Darwinian selection process (reviewed in reference 2). This model, first proposed by our group (32,33), accounts in a simple manner for the diversity of the syncytin genes found today. It was recently further sustained by the discovery that the primate Env-V gene that shows all the characteristic features of a bona fide syncytin gene in Old World monkeys has lost its fusogenic activity in higher primates-including humans-in which two other syncytins are present and active (34).…”
Section: Discussionmentioning
confidence: 95%
“…These new genes, depending on their fitness with regard to fulfilling placental functions, were selected in place of the previously captured envelopes, replacing them following a classical Darwinian selection process (reviewed in reference 2). This model, first proposed by our group (32,33), accounts in a simple manner for the diversity of the syncytin genes found today. It was recently further sustained by the discovery that the primate Env-V gene that shows all the characteristic features of a bona fide syncytin gene in Old World monkeys has lost its fusogenic activity in higher primates-including humans-in which two other syncytins are present and active (34).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the dynamic expression changes of syncytin-1, e.g., reduced mRNA and protein levels in preeclamptic placentas, is also closely associated with the changes in the methylation of 5′ LTR that serves as part of promoter of syncytin-1 gene [9, 17]. Potential involvements of syncytin-1 expression in the dysfunction of preeclamptic placenta are readily explained by its fusogenic and nonfusogenic activities [8, 18]. The close genomic location of PEX1, GATAD1 and syncytin-1 raised the possibility for a complex co-regulation of these genes by a concerted epigenetic program.…”
Section: Discussionmentioning
confidence: 99%
“…Syncytiotrophoblasts are formed via the fusion of cytotrophoblasts. Accumulated data indicated that syncytin-1, encoded by human endogenous retroviral family W Env(C7), member 1 (HERVWE1), mediates the fusion of cytotrophoblasts to form the multinucleated syncytiotrophoblasts [8]. Syncytin-1 is specifically expressed in placental trophoblast linage [9].…”
Section: Introductionmentioning
confidence: 99%
“…This locus harbors a member of the HERV-W family with an open reading frame in the env gene that encodes a protein denoted syncytin. This protein is highly expressed in the syncytiotrophoblast layer of the human placenta and appears to have been functionally adopted by the human host for fusion of trophoblast cells and thus contributing to the formation of the syncytiotrophoblast layer” [2022]. Thus, HERVs are helpful for the proper formation of the placenta and are involved in the suppression of rejection of fetal tissues.…”
Section: Data On the Activity Of Human Endogenous Retrovirusesmentioning
confidence: 99%